Processo de engenharia de domínio para aplicações em cadeias de suprimentos que utilizam de identificação por radiofreqüência (RFID) - Campos, Leonardo Barreto (Universidade Federal de São Carlos, 2007)
The Radio Frequency Identification RFID has opened a new phase in Supply Chain Management that can be controlled with precision and agility. Through this new technology is possible that Supply Chain members exchange informations in real time about stock, replace request, location of the products, and business strategy. However, the Radio Frequency Identification do not considered by software reuse and component-based development processes. In this sense, the Domain Engineering presents one solution to collecting, organizing, and storing past experience in building news systems used to reduce costs in RFID-based software development. Thus, this work presents an Domain Engineering Process based on a well defined set of guidelines and steps to RFID-based software engineering Systems in Supply Chain. We showed as results three Domain Engineering phases and one study case of the Supermarket Supply Chain.
Keywords: Engenharia de software; Software - desenvolvimento; Reuso; Cadeia de suprimentos; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO